Coping during the COVID-19 pandemic: A mixed methods approach to understand how social factors influence coping ability. Issue 10 (October 2022) - Chankasingh, Kyle; Booth, Amy; Albert, Arianne; Kaida, Angela; Smith, Laurie W.; Racey, C. Sarai; Gottschlich, Anna; Murray, Melanie C.M.; Sadarangani, Manish; Ogilvie, Gina S.; Galea, Liisa A.M.; Brotto, Lori A.
Abstract: The COVID-19 pandemic and public health protection measures aimed at mitigating the transmission of the virus have both resulted in tremendous physical and mental health impacts. The study at hand used a gender-based analysis and social determinants of health approach to investigate which communities had trouble coping during times of strict protection measures and symptoms and strategies employed during the COVID-19 pandemic. Participants were recruited from previously established cohorts as a part of the COVID-19 Rapid Evidence Study of a Provincial Population-Based Cohort for Gender and Sex (RESPPONSE) study. Being a young adult, female, woman, gender diverse, low-income earner or LGBTQ/2S+ was significantly associated with not being able to cope during the first wave of the pandemic. The effects for females, women, and gender diverse were attenuated yet still significant when controlling for various covariates. Those who reported not coping were more likely to present maladaptive coping symptoms and strategies. Our findings demonstrate the need to support marginalized communities in coping with the current ongoing COVID-19 pandemic and build proactive support for future pandemics. Abstract : Gender identity; Mental health; Social determinants of health; Adaptation; Psychological.